2019
DOI: 10.1016/j.heliyon.2019.e01126
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diet and weak cadmium stress affect the survivability of Caenorhabditis elegans and its resistance to severe stress

Abstract: Stress may have negative or positive effects in dependence of its intensity (hormesis). We studied this phenomenon in Caenorhabditis elegans by applying weak or severe abiotic (cadmium, CdCl2) and/or biotic stress (different bacterial diets) during cultivation/breeding of the worms and determining their developmental speed or survival and performing transcriptome profiling and RT-qPCR analyses to explore the genetic basis of the detected phenotypic differences. To specify weak or severe stress, developmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Therefore, in wheat, the target genes of our candidate small RNAs are correlated with the metabolism of cadmium, thereby validating our prediction. As for peptidyl-serine dephosphorylation, although few publications report the functional role of such biological processes in plants, in 2019, a specific study on Caenorhabditis elegans confirmed that such biological processes are correlated with weak cadmium stress via complex microbiological regulation, thereby validating our prediction (Dölling et al, 2019).…”
Section: Functional Enrichment Analyses On Target Genes Of Demssupporting
confidence: 74%
“…Therefore, in wheat, the target genes of our candidate small RNAs are correlated with the metabolism of cadmium, thereby validating our prediction. As for peptidyl-serine dephosphorylation, although few publications report the functional role of such biological processes in plants, in 2019, a specific study on Caenorhabditis elegans confirmed that such biological processes are correlated with weak cadmium stress via complex microbiological regulation, thereby validating our prediction (Dölling et al, 2019).…”
Section: Functional Enrichment Analyses On Target Genes Of Demssupporting
confidence: 74%
“…We were curious if the increased survivability on GSL microbes was due to a general induction of stress response to a foreign bacterium. E. coli HT115 is a weak biotic stressor that, perhaps counterintuitively, can enhance survival of C. elegans under certain stressed conditions [ 51 ]. The laboratory strain of C. elegans (N2) fed on HT115 showed a mixed response to GSL water after 5 min (ANOVA, diet: Chi Sq = 0.0131, d.f.…”
Section: Great Salt Lake Microbes Increase Nematode Survival To High ...mentioning
confidence: 99%
“…However, these experiments in the C. elegans stress response field lack standardization, creating results that are often difficult to interpret in the context of similar research. Experimental variables like stressor dose (e.g., acute vs. chronic), culture conditions, age at stress exposure, strain of bacterial food source, and method of stressor delivery can meaningfully impact the stressor dose needed to achieve a specific health outcome, activation of stress response pathways, and longevity of the organism [57], which can in turn significantly affect both experimental outcomes and biological interpretation of a study. This is particularly important for building an accurate understanding of biology of stress response by examining the body of evidence from experiments across different projects and laboratories.…”
Section: Introductionmentioning
confidence: 99%